The Role Of Agricultural Extensioners In Empowering Farmers (Case Study Of Pad Rice Farmers In Waitoso Village) - Lan S. Tambipessy (International Journal of Economics, Business and Innovation Research, 2023)
This study aims to determine the role of agricultural extension workers in empowering lowland rice farmers in Waitoso Hamlet . The analysis was performed using the SPSS descriptive test . In this study the SPSS descriptive test was used to determine the assessment obtained previously . The results showed that the role of extension workers was as a Facilitator, Motivator, and Communicator where the results of the analysis proved that there was a change in behavior in farming.